Speech Recognition Systems: From Statistical Models to Neural Networks - Asha N, (AG Volumes, 2025)
The development of the Speech Recognition Systems has been greatly advanced as compared to the initial statistical and rule-based framework to the neural network architecture. This review gives a thorough discussion of the development of the Automatic Speech Recognition (ASR) in terms of acoustic-phonetic and pattern recognition systems, N-gram models, Hidden Markov Models (HMM), and Gaussian Mixture Models (GMM). It points to the drawbacks of statistical analysis, including the scarcity of data, and the lack of contextual modeling, which encouraged people to switch to neural language models. The paper also discusses the development of Deep Neural Networks (DNN), Recurrent Neural Networks (RNN), Long Short-Term Memory (LSTM), Transformer-based architectures as well as end-to-ends models like CTC and attention mechanisms. Other recent developments such as self-supervised learning, hybrid systems and multilingual ASR are also explained using a wide literature review. The paper highlights the achievement in the performance in terms of a reduction in the Word Error Rate (WER) and presents the main challenges, such as noise robustness, low-resource languages, computational efficiency and ethical concerns.